Implementation of Project-Based Physics Learning to Improve Science Process Skills of 11th Grader at SMAN 1 Majene - Ilmi, Muhammad Rasikh; Amin, Bunga Dara (Jurnal Pendidikan MIPA, 2022)
Type of this research is a pre-experimental with One Group Pretest-Posttest research design. This research conducted to determine the improvement of students' science process skills after the implementation of project-based learning physics on static fluid material. The population of this study is all students of grade XI MIPA SMAN 1 Majene for the academic year 2021/2022 with the sample taken from class XI MIPA 1 with a total of 26 students. Science Process Skills of students are measured by using a test instrument. The results of this research indicate that there is an increase in the Science Process Skills of students on the observing indicator with an n-gain score is 0.56 and the planning experiment/project is 0.57 so that both were in the medium category. The indicator asking questions also increased with an n-gain score is 0.76 and the indicator applying concept is 0.84 so that both were in the high category. In general, the science process skills of students have increased with an n-gain score is 0.68 which is in the medium category. Keywords: physics learning, project based learning, science process skills. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1367-1375